2011
DOI: 10.1103/physrevb.84.024107
|View full text |Cite
|
Sign up to set email alerts
|

Native defects in LiNH2: A first-principles study

Abstract: Native defects in lithium amide (LiNH 2 ), a promising candidate for hydrogen storage, are investigated by first-principles calculations based on density functional theory. We examine the structural properties and formation energies of H-, Li-, and N-related defects in all possible states. We find that the dominant H-and Li-related defects are in charged states, i.e., negatively charged H vacancy (V H − ), positively charged H interstitial (H i + ), negatively charged Li vacancy (V Li − ), and positively charg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 50 publications
(79 reference statements)
1
10
0
Order By: Relevance
“…Other groups have recently reported first-principles calculations for native defects in LiNH 2 , using methodologies similar to ours. [26][27][28] The calculated formation energies and migration barriers of individual hydrogen-, lithium-, and nitrogen-related defects reported by Wang et al 28 are in close agreement with our results (to within 0.1 eV for most defects, with a maximum deviation of 0.2 eV in the case of V − H , our value being lower). Comparing to the results of Hazrati et al, 27 the deviations are somewhat larger (up to 0.4 eV), for which we cannot offer an explanation.…”
Section: Nitrogen-related Defectssupporting
confidence: 92%
See 1 more Smart Citation
“…Other groups have recently reported first-principles calculations for native defects in LiNH 2 , using methodologies similar to ours. [26][27][28] The calculated formation energies and migration barriers of individual hydrogen-, lithium-, and nitrogen-related defects reported by Wang et al 28 are in close agreement with our results (to within 0.1 eV for most defects, with a maximum deviation of 0.2 eV in the case of V − H , our value being lower). Comparing to the results of Hazrati et al, 27 the deviations are somewhat larger (up to 0.4 eV), for which we cannot offer an explanation.…”
Section: Nitrogen-related Defectssupporting
confidence: 92%
“…Hazrati et al 27 also proposed that the decomposition process occurs at the surface with the formation of (H + i ,V − H ) Frenkel pairs. Wang et al, 28 on the other hand, did not provide any specific mechanism but suggested that the formation of H + i is the rate-limiting step in hydrogen mass transport.…”
Section: A Li-ion Conductionmentioning
confidence: 99%
“…Besides experimental studies on defect-related properties in cathode materials, theoretic calculations, especially first-principles methods based on density functional theory (DFT), have been demonstrated to be a powerful tool for addressing defects in solid. 27 , 28 Some researchers have studied point defects in LiMn 2 O 4 through computational methods. 20 , 21 , 29 32 As early as the 1990s, Islam’s group have studied Li- and Mn-related interstitials and vacancies in LiMn 2 O 4 using interatomic potential models.…”
Section: Introductionmentioning
confidence: 99%
“…Some preliminary results and partial conclusions of our work have been reported elsewhere. 25 Other research groups have also recently started investigating native defects, [26][27][28] but our study goes much further in identifying specific mechanisms that can explain the experimental observations. A detailed comparison with the previous papers will be addressed in Sections IV A 3 and V B.…”
Section: Introductionmentioning
confidence: 89%